Innovation and creative destruction - Pichler, Hanns (Naše gospodarstvo, 2010)
In trying to create the background and scientific ''environs'' when Schumpeter''s visionary Theory of Economic Development (1912) was published, classical and neoclassical thought as well as Marx''s Das Kapital had already been exposed to scholarly scrutiny by the learned community for some time. Rather, it is Schumpeter''s truly seminal interpretation of the capitalist process in which the entrepreneur as such takes centre stage as the pioneering and driving force in a dialectic sense- in fact, as sort of a villain or the antithesis to the market system. It serves as an element constantly striving to outmanoeuvre the competition and trick the given market conditions, thereby forever challenging the system itself. Schumpeter''s vision today, more than ever, can serve as a guide for any entrepreneurially oriented policy formulation.
Keywords: Schumpeter, Joseph Alois, 1883-1950; ekonomske teorije; podjetništvo; konkurenca; inovativnost; kreativnost; efficiency; učinkovitost; konkurenčnost